The Implementation of Single Picture to Teach Describing Things Orally at Vocational High School to Increase Speaking Ability - Nuril Huda; Oikurema Purwati (J-SHMIC: Journal of English for Academic, 2022)
Vocational High School could not fulfil completely the requirements of skilled workers to support Indonesia globally. So, this study is to describe the implementation of a single picture to teach describing things orally at vocational high school to increase speaking ability. This study used classroom action research which has planing, acting, observing and reflecting step. The data was collected using speaking performance tests for the quantitative and observation checklist, field notes, and questionnaires for the qualitative. In the first cycle, all students could not describe things well because they did not get treatment. In the second cycle, 23% of students were excellent, 60% were good, and only 12% were categorized poorly. It can be implied that a single picture could assist the students’ creativity in describing things orally and increase the speaking ability.